PENGARUH BELANJA KESEHATAN TERHADAP ANGKA HARAPAN HIDUP DI KABUPATEN/KOTA PEMEKARAN PERIODE TAHUN 1999 – 2008 : ANALISIS DATA PANEL - ROBBY SIRAIT; RATNA CHRISTIANINGRUM (Pusat Kajian Anggaran, 2016)
This research empirically analyzed the relationship between public health spending and Life expectancy at birth. The data was collected from 182 districs/cities segregation of the period 1999 to 2008 between 2009 and 2013. Life expectancy at birth as indicator of public health degree , were used as dependent variables. To analyze cross- districs/cities panel data, we used random effect model. The findings showed a positive relationship between public health spending and life expectancy at birth. But, the relationship between public health spending and life expectancy at birth not statistically significant.